Aspects of in situ, in vitro germination and mycorrhizal partners of Liparis loeselii - Illyés, Zoltán; Rudnóy, Szabolcs; Bratek, Zoltán (Acta Biologica Szegediensis, 2005)
Our present work investigated asymbiotic in vitro and symbiotic in situ germination of the rare and protected terrestrial orchid, Liparis loeselii (L.) Rich. as one of the possibilities for its conservation. Asymbiotic germination array was tested on four different asymbiotic media (different macroelement and organic nitrogen levels) in dark and light. Additionally the effect of cold-treatment was also investigated. In situ germination rate was moderate, protocorms was observed only in the close surroundings of adult L. loeselii individuals. The fungal partners of L. loeselii were identified by sequence analysis of the internal transcribed spacer (ITS) of nuclear ribosomal DNA (nrDNA). The ‘root segment technique’ was effective for isolation of only one species, Tulasnella (Epulorhiza), whereas using ‘in situ bating’ yielded isolates of both Tulasnella and Ceratobasidium (Rhizoctonia) species.